Analisis Faktor-Faktor Yang Mempengaruhi Struktur Modal Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2008 -2015 - Anthony Ghozali dan Ignatius Roni Setyawan (Universitas Tarumanagara, 2019)
Capital structure is one of the most important things that every company should concern about. As alongwith economic issues that recently happened in this past years, such as crisis, inflation, etc, this study aims to find out about the factors that affect the capital structure in the food and beverage sectors listed in the Indonesia Stock Exchange (BEI) in the year of 2008-2015. The data sample of 8 companies is collected by using financial statements from each company that issued by Indonesia Stock Exchange.. This study use multiple regression with Ordinary Least Square (OLS) method to examine the effect of profitability (return on asset), firm size, asset growth and liquidity on the capital structure (debt-to-equity ratio). The conclusion of this study indicate that profitability, firm size, asset growth and liquidity affect the capital structure simultaneously, meanwhile partially, profitability affect the capital structure while firm size, asset growth and liquidity not affect the capital structure.